2018
DOI: 10.1177/1747021818779496
|View full text |Cite
|
Sign up to set email alerts
|

Taking the perspective of the narrator

Abstract: Readers do not always adopt the perspective of the protagonist; however, they will under certain conditions. Experiments 1a and 1b showed that readers will take the perspective of the protagonist from the third-person point of view, but only when explicitly instructed to do so. Experiment 2 demonstrated that reading from the first-person point of view is a text-based manipulation that encourages readers to adopt the perspective of the protagonist. The results of Experiments 3a and 3b replicated the findings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 68 publications
5
11
0
Order By: Relevance
“…In another discourse processing study, Creer, Cook, and O’Brien [53] examined how narrator perspective (i.e., first-person, third-person) influenced processing of spatial inconsistencies embedded in texts. Across multiple self-paced line-by-line experiments, they found that under normal reading conditions, readers were disrupted by spatial inconsistencies involving the protagonist when texts were written in the first-person perspective, but not when they were written in the third-person perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another discourse processing study, Creer, Cook, and O’Brien [53] examined how narrator perspective (i.e., first-person, third-person) influenced processing of spatial inconsistencies embedded in texts. Across multiple self-paced line-by-line experiments, they found that under normal reading conditions, readers were disrupted by spatial inconsistencies involving the protagonist when texts were written in the first-person perspective, but not when they were written in the third-person perspective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Williams and colleagues [54] argued that changing the number of comprehension questions asked at the end of each passage may shift the coherence threshold, such that readers will either wait more or less time for validation processes to complete before they move on in the text. When comprehension questions were increased, the coherence threshold was high, meaning that the validation process had more time to complete before readers moved on to subsequent text (see also [53]). When comprehension questions were decreased, the coherence threshold was low, and readers waited very little time for validation to complete before moving on to subsequent information.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this focus on the protagonist, situation models include information about the protagonist’s goals, knowledge, and emotions (e.g., Gernsbacher et al, 1992; Greene et al, 1994; Huitema et al, 1993; Lea et al, 1998; Magliano et al, 2005; Magliano & Radvansky, 2001; McKoon et al, 1996; Suh & Trabasso, 1993). Given the centrality of the protagonist in the situation model, one issue of considerable interest has been the extent to which readers adopt the perspective of the protagonist when encoding new information (e.g., Albrecht et al, 1995; Black et al, 1979; Bower & Morrow, 1990; Creer et al, 2019; Morrow et al, 1987, 1989, 1990; O’Brien & Albrecht, 1992; Smith & O’Brien, 2012). For example, readers are sensitive to information about objects and goals relevant to the protagonist’s point of view (Cook et al, 2007; de Vega, 1995; Glenberg et al, 1987; Morrow et al, 1987, 1989).…”
mentioning
confidence: 99%
“…An implicit assumption in much of this work has been that incoming information, particularly spatial and goal information, is understood from the main character’s perspective (e.g., Black et al, 1979; Bower & Morrow, 1990; Morrow et al, 1990). However, in studies examining moment-to-moment reading, the finding has been that readers do not typically adopt the perspective of the protagonist; instead, they appear to approach the text from an omniscient perspective (Creer et al, 2019; O’Brien & Albrecht, 1992). But readers can and will adopt the perspective of the protagonist under certain text-based conditions (Brunyé et al, 2009; Child et al, 2018; Creer et al, 2019; Ferguson & Jayes, 2018; Franklin & Tversky, 1990; Hartung et al, 2017) and task-based conditions (Bortolussi et al, 2018; Kaakinen et al, 2002; Kaakinen & Hyöna, 2008; O’Brien & Albrecht, 1992; Pichert & Anderson, 1977; Smith & O’Brien, 2012; van Krieken, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation